Incentives, shocks or signals: Labour supply effects of increasing the female state pension age in the UK - Jonathan Cribb; Carl Emmerson; Gemma Tetlow (Institute for Fiscal Studies (IFS), 2013)
In 1995, the UK government legislated to increase the earliest age at which women could claim a state pension from 60 to 65 between April 2010 and March 2020. This paper uses data from the first two years of this change coming into effect to estimate the impact of increasing the state pension age from 60 to 61 on the employment of women and their partners using a difference-in-differences methodology. Our methodology controls in a flexible way for underlying differences between cohorts born at different times. We find that women's employment rates at age 60 increased by 7.3 percentage points when the state pension age was increased to 61 and their probability of unemployment increased by 1.3 percentage points. The employment rates of the male partners also increased by 4.2 percentage points. The magnitude of these effects, and the results from subgroup analysis, suggest they are more likely explained by the increase in the state pension age being a shock or through it having a signalling effect rather than them being due to either credit constraints or the effect of individuals responding to changes in their financial incentives to work. Taken together, our results suggest that the fiscal strengthening arising from a one-year increase in the female state pension age is 10% higher than a costing based on no behavioural change, due to additional direct and indirect tax revenues arising from increased earnings.
Keywords: H55; J21; J26; 330; early retirement age; labour supply; policy reform; retirement